2023
DOI: 10.3390/polym15122703
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of the Mechanical Performance of EPS Foam Core Sandwich Composites Used in Surfboard Design

Abstract: Surfboard manufacturing has begun to utilise Expanded Polystyrene as a core material; however, surf literature relatively ignores this material. This manuscript investigates the mechanical behaviour of Expanded Polystyrene (EPS) sandwich composites. An epoxy resin matrix was used to manufacture ten sandwich-structured composite panels with varying fabric reinforcements (carbon fibre, glass fibre, PET) and two foam densities. The flexural, shear, fracture, and tensile properties were subsequently compared. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…At the end of the study, they concluded that high foam density increased the mechanical properties of composites such as flexibility and fracture. 51 …”
Section: Introductionmentioning
confidence: 99%
“…At the end of the study, they concluded that high foam density increased the mechanical properties of composites such as flexibility and fracture. 51 …”
Section: Introductionmentioning
confidence: 99%